The Effect of Integrating Sports Games into English Education on Students’ Positive Psychology - Xiaoyan Fan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The limited research on the prospective benefits of incorporating sports games into English language learning hinders our understanding of how such integration may influence students' positive psychology. Addressing the need for empirical evidence, research conducted to check the effect of integrating sports games into English education on students' positive psychology. The author mainly used literature, questionnaire, test and mathematical statistics as research methods, and the Adolescent Psychological Resilience Scale and Middle School Students Coping Style Scale as test measurement tools, through the teaching test of sports game intervention, the test design of pre and post-test in the test class and the sample class is used to explore.The mean value of psychological resilience of the students in the test class before the test was 90.12, while the mean value of psychological resilience of the students in the test class after the test was 95.33, from T=-5.660, P=0.000<0.01, it can be seen that the psychological resilience of the students in the test class after the test has been significantly improved. The effect of sports game intervention on psychological resilience and coping style, the two test indicators of the scale, concluded that sports game intervention can effectively improve the frustration tolerance of middle school students. When helping each other, the games can be completed more smoothly, and sharing the happiness of success among students can also make their interpersonal relationship more harmonious. Therefore, the sports game intervention has a significant effect on the interpersonal auxiliary factors among middle school students. Understanding the impact of integrating sports games in English education can offer valuable insights for educators and policymakers seeking innovative approaches to promote students' well-being and academic achievement simultaneously